كواشف الاستقلال الموضعي في نظرية الاستجابة للفقرة ومدى تأثرها بقوة العلاقة الارتباطية بين الأبعاد ومستوى القدرة للمفحوصين - ابوشندي يوسف (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
هدفت هذه الدراسة إلى تفحص تأثير قوة العلاقة الارتباطية بين الأبعاد(0.0,0.5,0.9) ومستوى قدرة المفحوصين( منخفضة، متوسطة، عالية) على قدرة أربعة من كواشف الاستقلال الموضعي: Q3، Fisher Z، G2، ووسط معاملات الارتباط البينية على الكشف عن نسبة أزواج الفقرات المنتهكة لهذا الافتراض. وقد تم توليد استجابات ثلاث مجموعات من المفحوصين (10000 مفحوص لكل مجموعة تتوزع قدراتهم توزيع طبيعي) على اختبار ثلاثي البعد( يحتوي كل بعد على 40 فقرة أحادية البعد)، تختلف المجموعات فيما بينها في قوة الارتباط بين الأبعاد. ومن كل مجموعة تم اختيار ثلاثة مستويات لقدرات المفحوصين. بيَنت الدراسة عدم تأثر المؤشر G2 بتغير قوة الارتباط، وعدم تأثر المؤشر وسط معاملات الارتباط البينية عند قوة الارتباط (0.0, 0.5). أما المؤشران Q3، Fisher Z فلم يتأثرا فقط عند قوة الارتباط(0.0). وفيما يتعلق بتأثير مستوى قدرة المفحوصين, بيَنت النتائج أن نسبة أزواج الفقرات المنتهكة للاستقلال الموضعي لم تتغير عند استخدام المؤشر G2، وكانت تقل بنقصان مستوى قدرة المفحوصين عند استخدام المؤشرات: وسط معاملات الارتباط البينية، Q3، Fisher Z وقوة الارتباط بين الأبعاد 0.9. This study attempts to investigate the effects of the strength of the relationship between dimensions (0.0,0.5,0.9) and examinees’ ability levels (low, moderate, high) on ability of four indices: Q3, Fisher Z, G2 and the mean of pair twice correlation coefficient testing locally independent items for the data generated from locally dependent items. Three groups of examinee (10000 each) responses are generated on the basis of three dimensional tests (each dimension contains 40 uni-dimensional items); the groups are different in the strength of inter-dimensional correlation. For each group, three levels of examinees’ ability are chosen. The results obtained show that the percentage of local item pairs does not change on the G2, though the Inter-dimensional correlation strength varies. And the index means of the pair twice correlation coefficient ranks second, followed by the indices Fisher Z and Q3. This study also reveals that the percentage of local item pairs does not vary when the level of examinees’ ability varies by using G2 index.; the percentage decreases when Fisher Z, Q3 is used, though the inter-dimensional correlations are different.